Pattern of dental needs and advice on Twitter during the COVID-19 pandemic in Saudi Arabia - Khalifa S. Al-Khalifa; Eman Bakhurji; Hassan S. Halawany; Esraa M. Alabdurubalnabi; Wejdan W. Nasser; Ashwin C. Shetty; Shazia Sadaf (BMC, 2021)
Abstract Aim To compare and evaluate the influence of the COVID-19 outbreak on tweets related to dental treatment needs and advice of Saudi Twitter users in 2020 by comparing them to the same time-period in 2019. Methods Eight independent searches based on dentistry related keywords: "teeth, mouth and gingiva" were carried out within the timeframe between the 23rd of March and the 21st of June for the years 2020 and 2019. Extracted tweets were analyzed by two calibrated examiners as tweets containing expressed dental needs and tweets for dental advice, while spam tweets were excluded. Descriptive analysis was performed to present the overview of the findings using SPSS. Bivariate analysis was performed with Pearson's Chi Square, Fisher's Exact test and Mann-Whitney U test. Statistical significance was set at p ≤ 0.05. Results A total of 595 tweets from the year 2019 and 714 tweets from the year 2020 were obtained. Overall, combined dental needs and advice tweets, retweets, likes, and replies were higher in 2020 compared to 2019. Dental needs tweets were higher in 2020 compared to 2019, while dental advice tweets were lower in 2020 compared to 2019. Statistically significant differences were found between 2020 and 2019 with regards to dental needs well as with dental advice (p < 0.05). In addition, statistically significant differences were found between 2019 and 2020 with presence of pain, urgency of the dental need and type of advisor (p < 0.05). Conclusion An obvious impact of the pandemic can be seen in the form of increased self-reported dental needs, pain and urgency among the public in Saudi Arabia. This study highlights the importance of social media, specifically Twitter, in expressing the public needs and utilizing it as a platform for education and advice.